Do ecological effects on recidivism vary by gender, race, or housing type? - McNeeley, Susan M. (Crime & delinquency, 2018)
Several studies show that recidivism is influenced by the context of neighborhoods in which offenders live after leaving prison. However, the research on this topic is mixed, with many studies finding inconsistent or null neighborhood effects. This study addresses this inconsistency by examining whether neighborhoods affect recidivism differently based on offenders’ housing situation or personal characteristics (i.e., gender, race). The results of the multilevel logistic regression analyses show that neighborhood characteristics were significantly related to rearrest among minority offenders but not White offenders, and among offenders living in private residential housing but not those living in community-based facilities. These results help to explain the mixed findings in the literature and highlight the complexity of the relationship between neighborhood context and recidivism.